Sovereign risk and bank risk-taking - Anil Ari (European Central Bank (ECB), 2016)
In European countries recently hit by a sovereign debt crisis, the share of domestic sovereign debt held by the national banking system has sharply increased, raising issues in their economic and financial resilience, as well as in policy design. This paper examines these issues by analyzing the banking equilibrium in a model with optimizing banks and depositors. To the extent that sovereign default causes bank losses also independently of their holding of domestic government bonds, under-capitalized banks have an incentive to gamble on these bonds. The optimal reaction by depositors to insolvency risk imposes discipline, but also leaves the economy susceptible to self-fulfilling shifts in sentiments, where sovereign default also causes a banking crisis. Policy interventions face a trade-off between alleviating funding constraints and strengthening incentives to gamble. Liquidity provision to banks may eliminate the good equilibrium when not targeted. Targeted interventions have the capacity to eliminate adverse equilibria.
Keywords: E44; E58; F34; G21; H63; 330; bank risk-taking; Eurozone; financial constraints; sovereign debt crises